Work-Integrated Learning to Improve Work Readiness of Vocational Education in School and Madrasah - Wahyuningsih, Rintatik; Joyoatmojo, Soetarno; Wardani, Dewi Kusuma; Noviani, Leny (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2025)
Work readiness is a crucial competency for Vocational Education (VE) students in both schools and madrasahs to be competitive in the job market. Although VE institutions are expected to provide a balanced mix of theoretical and practical training, many graduates still fall short of industry expectations, both during internships and after graduation. A lack of curriculum alignment with industry needs and the suboptimal use of production units as practical learning media causes this gap. This study examines teachers' efforts to enhance students' work readiness through a Work-Integrated Learning (WIL) approach. A mixed-methods design with a sequential exploratory strategy was employed. In the quantitative phase, questionnaires were distributed to 120 respondents (students, teachers, and industry workers) to measure work readiness indicators such as technical skills, communication, work ethic, and problem-solving. The qualitative phase included classroom observations, in-depth interviews, and literature reviews to enrich the analysis. The results show that WIL significantly improves work readiness: technical skills increased by 23%, communication by 18%, and problem-solving by 15%, with statistical significance (p-value = 0.000) based on the Wilcoxon test. The consistency of these improvements across regions indicates that WIL has practical relevance and high scalability potential. The novelty of this research lies in its dual focus on vocational schools and madrasahs, which are still rarely explored in previous literature. By combining quantitative and qualitative approaches, this study confirms that WIL can be systematically integrated into the VE curriculum to enhance graduates' competitiveness in a dynamic labor market.